Association of Heart Rate Variability With Cognitive Performance: The Multi‐Ethnic Study of Atherosclerosis. Issue 7 (9th April 2020) - Schaich, Christopher L.; Malaver, Diego; Chen, Haiying; Shaltout, Hossam A.; Zeki Al Hazzouri, Adina; Herrington, David M.; Hughes, Timothy M.
Abstract : Background: Heart rate variability (HRV) is associated with vascular risk factors for dementia, but whether HRV is associated with specific domains of cognitive performance is unclear. Methods and Results: In the Multi‐Ethnic Study of Atherosclerosis (N=3018; mean age 59.3±9.2 years), we assessed the relationship of 10‐second HRV to scores on tests of global cognitive performance (Cognitive Abilities Screening Instrument), processing speed (Digit Symbol Coding), and working memory (Digit Span). HRV was computed as the SD of normal‐normal intervals (SDNN) and root mean square of successive differences (RMSSD) at Exam 1 (2000–2002) and Exam 5 (2010–2012). Cognitive tests were administered at Exam 5. We report regression coefficients (β [95% CI]) representing cognitive test score change per 2‐fold increase in HRV. After adjustment for age, race/ethnicity, sex, education, apolipoprotein E genotype, and cardiovascular risk factors and incident disease, higher Exam 1 (β=0.37 [0.06, 0.67]) and Exam 5 (β=0.31 [0.04, 0.59]) SDNN were associated with better Cognitive Abilities Screening Instrument performance. Higher Exam 1 (β=0.80 [0.17, 1.43]) and Exam 5 (β=0.63 [0.06, 1.20]) SDNN, and Exam 5 RMSSD (β=0.54 [0.01, 1.08]) were associated with better Digit Symbol Coding performance. Finally, higher Exam 5 SDNN was associated with better Digit Span performance (β=0.17 [0.01, 0.33]). Associations were attenuated after adjustment for resting heart rate. Conclusions: Higher HRV is generally associated with better cognitive performance in this multi‐ethnic cohort of aging adults, and further study of the relationship of autonomic function to cognition is warranted.